Electrochemical characteristics of the La0.9Sr0.1Sс0.4Mn0.6O3 – δ cathode contacting the La0.9Sr0.1SсO3 – δ proton-conducting electrolyte - Bervitskaya, Olga S.; Ichetovkina, Victoria A.; Bobro, Mark S.; Stroeva, Anna Y.; Kuzmin, Anton Valerievich (Электрохимическая энергетика)
In this work, the material La0.9Sr0.1Sс0.4Mn0.6O3 – δ was synthesized using the citrate-nitrate method. The electrochemical characteristics of the material were studied using impedance spectroscopy on symmetric cells and compared with the model Pt cathode contacting the proton-conducting electrolyte. It was shown that the polarization resistance of the investigated material is approximately two orders lower than that of the model Pt electrode. Based on this, the composition of La0.9Sr0.1Sс0.4Mn0.6O3 – δ can be proposed as a promising cathodic material for proton ceramic fuel cells.